SISTEM PEMESANAN BARANG MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN REORDER POINT (ROP) DI PT KIMIA FARMA PLANT SEMARANG - Ardan Muchammad; Novita Mariana (STEKOM PRESS, 2023)
Every sale of goods, sales report the number of goods sold to the warehouse admin. Because of the many types of goods being sold, sometimes the warehouse admin forgets about which items are almost out of stock and should be ordered. The aim of this research is to produce a goods ordering system with the EOQ and ROP control methods to overcome the occurrence of stockouts. The author uses the research object of employees who work at PT Kimia Farma Plant, namely sales, warehouse department, admin and HRD. With this system, the warehouse admin can see the number of items in real time. The EOQ method generates a report on the number of economic purchases (EOQ), the total costs that must be incurred by the company to reorder an item, the duration of the EOQ, up to the reorder point (ROP).